2000
DOI: 10.1002/(sici)1098-1063(2000)10:1<88::aid-hipo10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol, memory, and hippocampal function: A review of recent findings

Abstract: For well over a century, ethanol was believed to exert its effects on cognition and behavior by producing a ubiquitous depression of central nervous system activity. A general disruption in brain function was consistent with the belief that ethanol's effects on cognition and behavior were also quite general. Substantial evidence now indicates that ethanol produces a host of selective effects on neural activity, resulting in regional differences in ethanol's effects in the brain. Consistent with such evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(109 citation statements)
references
References 99 publications
(123 reference statements)
3
105
0
1
Order By: Relevance
“…Nicotine acts primarily at nACh receptors, whereas ethanol acts on a wide variety of targets that include nAChRs (Bowers et al 2005;Escher and Mittleman 2004;Larsson et al 2002;Melia et al 1996;Meyerhoff et al 2006;Wehner et al 2004;White et al 2000). Thus, ethanol may directly interact with nicotine by altering nAChR function; in support, ethanol stabilizes the open state of nAChRs, producing a twofold leftward shift in the acetylcholine response curve (Forman and Zhou 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine acts primarily at nACh receptors, whereas ethanol acts on a wide variety of targets that include nAChRs (Bowers et al 2005;Escher and Mittleman 2004;Larsson et al 2002;Melia et al 1996;Meyerhoff et al 2006;Wehner et al 2004;White et al 2000). Thus, ethanol may directly interact with nicotine by altering nAChR function; in support, ethanol stabilizes the open state of nAChRs, producing a twofold leftward shift in the acetylcholine response curve (Forman and Zhou 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ethanol may directly interact with nicotine by altering nAChR function; in support, ethanol stabilizes the open state of nAChRs, producing a twofold leftward shift in the acetylcholine response curve (Forman and Zhou 1999). Ethanol also acts on many other receptors, including GABA A and glutamatergic NMDA receptors (for review see White et al 2000), and nAChRs have been shown to modulate both GABAergic and glutamatergic function (Alkondon and Albuquerque 2001;Gray et al 1996). Thus, ethanol and nicotine may interact by modulating GABAergic and glutamatergic function.…”
Section: Discussionmentioning
confidence: 99%
“…whole-cell currents | null mutant mice A lcohol-induced memory deficits have been well documented in humans, as well as animal studies (1). Long-term potentiation (LTP) is widely accepted as a cellular mechanism underlying learning and memory in the hippocampus, as well as other brain regions (2), and is dependent upon NMDA receptor (NMDAR) activation (3).…”
mentioning
confidence: 99%
“…Recent research using animal models has shown that alcohol profoundly suppresses the activity of pyramidal cells in the region of the hippocampus that has been associated with ability to form new explicit memories [7]. Much is known about the effects of alcohol on decrements in motor performance, and there is also compelling evidence to indicate that acute alcohol use impairs the performance of frontal lobe-mediated tasks such as those that require judgment and impulse control [8].…”
Section: Central Pattern Generators (Cpgs)mentioning
confidence: 99%